"A conscious memento": The literary afterlives of Henry James's Lamb House. (2nd September 2018) - Boyd, Ailsa
Abstract : In 1896, the novelist Henry James became captivated by Lamb House, a Georgian, red brick house at the top of a cobbled street in Rye with a unique, bow-windowed "garden room." Restoring and decorating it sympathetically, it became his main home for the rest of his life, a comfortable retreat where the observer of society could himself entertain guests. The house and garden feature in subsequent novels, and he worked in the garden room, revising his novels and tales for the New York Edition, a re-examination of his whole career. After James's death, his friend E. F. Benson moved in, using Lamb House as the inspiration for Mallards in his comic Mapp and Lucia novels (1920–1935). In 1940, the garden room was obliterated by a bomb, which nearly destroyed the house. However, what Edith Wharton called "the centre of life at Lamb House, " still survives in various recreations and re-imaginings, from the novels written by its inhabitants to memoirs and fictions by more recent writers and television adaptations. James utilized the distancing and memorializing effects of nostalgia in his own work, to create a living, modernist interaction with the past, the "conscious memento." Thus, fictional representations and the writing of place can be part of intangible heritage, enabling the survival of architecture beyond its physical presence.